GENERAL RULES AND THEORETICAL FEATURES OF THE REGULATION OF ONLINE LAW AND THE ISSUE OF LIABILITY (World Bulletin of Management and Law, 2025)
This article provides an overview of the general rules and theoretical features of the issue of online legal regulation and liability, as well as an analysis of the indicators of online network usage by regions of the world